Using virtual reality to support the design of work systems in 3P workshops: a use case from the automotive industry - Hertwig, Alma F.; Brandewiede, André; Feufel, Markus A. (Frontiers in Virtual Reality, 2024)
In a context of increased competition due to growing customer centricity and product diversity, the automotive industry is challenged to improve the efficiency of its production processes. The design of the work system plays a decisive role in this. Virtual technologies are seen as having great potential to support this process. In this field study, the use of a user-centered Virtual Reality (VR) application for planning workshops was investigated. Over several weeks, the technology was used in the productive 3P workshop. The focus was on the acceptance of the professional groups, which is crucial for the successful integration of VR technology. To evaluate this, a questionnaire study based on the Unified Theory of Acceptance and Use of Technology (UTAUT), task-technology fit, and User Experience Questionnaire (UEQ) was conducted with 83 participants. Results show that VR technology can be used to conduct 3P workshops and enable acceleration. Determinants of user acceptance are task-technology fit, user experience of the software and how well occupational groups are supported by the technology. Age and prior VR experience did not have a significant impact on user acceptance. The results are discussed with respect to their theoretical and practical implications and limitations are identified.